2006
DOI: 10.1152/ajpcell.00364.2005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracellular electrolyte concentrations during apoptosis induced by UV irradiation of human myeloblastic cells

Abstract: Decreases in the intracellular concentrations of both K(+) and Cl(-) have been implicated in playing a major role in the progression of apoptosis, but little is known about the temporal relationship between decreases in electrolyte concentration and the key events in apoptosis, and there is no information about how such decreases affect different intracellular compartments. Electron probe X-ray microanalysis was used to determine changes in element concentrations (Na, P, Cl, and K) in nucleus, cytoplasm, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
2
26
0
1
Order By: Relevance
“…Water measurement methods based on population analysis include gradient density centrifugation (5,127), NMR (108), quantification of intracellular markers (61,63), or drying and weighing (98). Microscopic approaches would require determination of the refractive index, which can be accomplished by quantitative phase microscopy (86); indeed, Model and Schonbrun (86) presented evidence that staurosporine and actinomycin D induce dehydration (AVD) as well as loss of dry mass.…”
Section: Undetected Apoptotic Body Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Water measurement methods based on population analysis include gradient density centrifugation (5,127), NMR (108), quantification of intracellular markers (61,63), or drying and weighing (98). Microscopic approaches would require determination of the refractive index, which can be accomplished by quantitative phase microscopy (86); indeed, Model and Schonbrun (86) presented evidence that staurosporine and actinomycin D induce dehydration (AVD) as well as loss of dry mass.…”
Section: Undetected Apoptotic Body Releasementioning
confidence: 99%
“…Apparently, AVD can be an early (5,8,15,28,34,49,53,81) or a late (26,60,85,90,117) response, depending on the particular system. A few exceptions to the rule that AVD must accompany apoptosis have also been described (11,13,56,65,121,127); nevertheless, it appears that, in the vast majority of apoptotic models, AVD does occur sooner or later.…”
mentioning
confidence: 99%
“…Depending on the model system employed to study cell death, a late increase in intracellular sodium has also been reported during apoptosis. It was recently shown by x-ray microanalysis that staurosporine-induced [107] and UV-induced [108] apoptosis in U-937 cells resulted in an increase in intracellular sodium that occurs late in the cell death process. In these studies, the investigators could divide the changes in cellular elemental composition into two stages: an early stage characterized by a decrease in intracellular potassium concomitant with cell shrinkage and prior to caspase-3 activity or nuclear changes; and a later stage of decreased potassium content coupled with an increase in sodium content resulting from the activation of caspase-3.…”
Section: Sodium As a Signal During Apoptosismentioning
confidence: 99%
“…Several studies point out that it is not the specific ion per se that is involved in the apoptotic signaling, but rather a decrease in intracellular ionic strength (Arrebola et al, 2006(Arrebola et al, , 2005a(Arrebola et al, , 2005bHughes et al, 1997;Perez et al, 2000). Furthermore, increase in ionic strength has been shown to block the cytochrome c activated caspase-3 pathway (Hampton et al, 1998 (Ye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%